2004
DOI: 10.1017/s0021932004006893
|View full text |Cite
|
Sign up to set email alerts
|

hiv/aids in rural india: context and health care needs

Abstract: Primary research on HIV/AIDS in India has predominantly focused on known risk groups such as sex workers, STI clinic attendees and long-distance truck drivers, and has largely been undertaken in urban areas. There is evidence of HIV spreading to rural areas but very little is known about the context of the infection or about issues relating to health and social impact on people living with HIV/AIDS. In-depth interviews with nineteen men and women infected with HIV who live in rural areas were used to collect e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(85 citation statements)
references
References 16 publications
4
80
1
Order By: Relevance
“…She often chooses the former. As a result, three quarters of HIV-positive women in India were found to be infected within a few years of marriage (Pallikadavath et al, 2005;Solomon et al, 2004). Such attributes of traditional Gujarat are in many ways contributing to secrecy around HIV, where testing is either discouraged or unknown among many inhabitants (Zelaya et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…She often chooses the former. As a result, three quarters of HIV-positive women in India were found to be infected within a few years of marriage (Pallikadavath et al, 2005;Solomon et al, 2004). Such attributes of traditional Gujarat are in many ways contributing to secrecy around HIV, where testing is either discouraged or unknown among many inhabitants (Zelaya et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In the general population, 40% (1 million) live in various slum pockets and almost 80% (2 million) are poorly educated (Pallikadavath, Garda, Apte, Freedman & Stones, 2005). It is hypothesised that because of the high traffic of rural commuters to and from cities like Ahmadabad 255 km to the north (where 13% of commercial sex workers are HIV-infected) and Mumbai 263 km to the south (where 54% of commercial sex workers are HIV-infected and injection drug use is more accessible), the epidemic may build a stronghold here (Fung et al, 2007;Madhivanan et al, 2005;Pallikadavath et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Further, it is associated with all forms of stigma, namely felt, internalised and vicarious stigma (Steward et al, 2008). For example, the fear of mistreatment in health settings, potential loss of social status for self and family, possible loss of job and rejection from spouse, reported among men with HIV influence their disclosure decisions and form the basis for felt and self stigma (Bharat et al, 2001;Pallikadavath, Garda, Apte, Freedman, & Stones, 2005). Similarly, the anticipated negative impact on children's school admission and likely rejection from spouse/inlaws, reported among HIV positive women affect their decisions to share information on HIV status with others (Thomas, Nyamathi & Swaminathan, 2008;Bharat et al, 2001)..…”
Section: Article Originalmentioning
confidence: 99%
“…Similarly, the anticipated negative impact on children's school admission and likely rejection from spouse/inlaws, reported among HIV positive women affect their decisions to share information on HIV status with others (Thomas, Nyamathi & Swaminathan, 2008;Bharat et al, 2001).. Managing information of one's own HIV status or of a close family member is thus important as a strategy to escape from enacted stigma and its social costs (Pallikadavath et al, 2005;Steward et al, 2008). High disclosure-related concerns are supported by quantitative studies of stigma (Subramanian, Gupte, Dorairaj, Periannan & Mathai, 2009;Thomas, Rehman, Suryanarayanan, Josephine, Dilip, Dorairaj et al, 2005) with at least one study reporting significantly higher disclosure concerns among positive women (91%) than men (82%) (Subramanian et al, 2009).…”
Section: Article Originalmentioning
confidence: 99%
“…The ABC of prevention -Abstain, Be faithful, use a Condom -is easier for some women to practice than others. In studies from India (Gangakhedar et al, 1997;Pallikadavath et al, 2004) to sub-Saharan Africa (Doyal, 1994;Gupta, 2002;Hamblin and Reid, 1991;Rankin et al, 2005) evidence has shown that a high percentage of women were infected with HIV by their husbands. Abstinence is problematic within a marriage for fear of being stigmatised as having something to protect against, or accusatory and thus inferring a lack of trust within the relationship.…”
mentioning
confidence: 99%